2005
DOI: 10.1037/0021-9010.90.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Emotions in Injustice Perceptions and Retaliation.

Abstract: Although organizational justice scholars often describe unfairness as an emotionally laden experience, the role of emotion is underresearched. In a study of individuals who experienced being laid off (N = 173), the authors found that outcome favorability interacts with both procedural and interactional justice to predict participants' emotions. The pattern of interaction differed for inward-focused (i.e., shame and guilt) and outward-focused (i.e., anger and hostility) negative emotions. Attributions of blame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
400
4
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(460 citation statements)
references
References 57 publications
31
400
4
9
Order By: Relevance
“…The findings of Van den Bos are important because they support the ideas that (a) justice is in the eye of the beholder and thus subject to people's subjective and affective experiences (see also Barclay et al 2005;De Cremer 2007), and (b) mood impacts on fairness judgments under specific circumstances (i.e. when uncertainty about fairness information is high).…”
supporting
confidence: 54%
“…The findings of Van den Bos are important because they support the ideas that (a) justice is in the eye of the beholder and thus subject to people's subjective and affective experiences (see also Barclay et al 2005;De Cremer 2007), and (b) mood impacts on fairness judgments under specific circumstances (i.e. when uncertainty about fairness information is high).…”
supporting
confidence: 54%
“…111)." It appears, then, that researchers lack a clear understanding of when perceived unfairness translates into retaliation and why unfairness recipients pursue or inhibit retaliation.Some justice research has looked into affect as an explanation for the inconsistent relation between unfair treatment and retaliation (Barclay, Skarlicki, & Pugh, 2005;Bembenek et al, 2007;Bies & Tripp, 1996;De Cremer, 2007). This research has shown that negative emotions (e.g., anger, disappointment) accompany retaliation as a response to perceived unfairness, but the research has not addressed when and why people sometimes pursue and sometimes inhibit retaliation.…”
mentioning
confidence: 99%
“…No entanto, a injustiça parece conter mais intensamente aspectos emocionais visto que ela é freqüentemente associada ou considerada como um sentimento (Barclay, Skarlicki & Pugh, 2005;Weiss, Suckow & Cropanzano, 1999). Neste sentido pressupomos que há uma assimetria na intensidade dos componentes afetivos entre as representações sociais da justiça e injustiça.…”
Section: Organização Afetiva Das Representações Sociaisunclassified
“…No entanto supõe-se que a L. Spadoni injustiça é mais intensamente afetiva do que a justiça a ponto de ser considerada por alguns autores da psicologia como um sentimento (Barclay, Skarlicki & Pugh, 2005;Weiss, Suckow & Cropanzano,1999).…”
unclassified